Cationic starch flocculants as an alternative to synthetic polymers in geotextile tube dewatering - Khachan, M. M.; Bhatia, S. K.; Bader, R. A.; Cetin, D.; Ramarao, B. V. (ICE PUBLISHING, 2014)
Polyacrylamide-based conditioners have become an essential component of the geotextile tube dewatering processes. These conditioners act as flocculants, binding fine sediments through charge neutralisation and particle bridging, resulting in faster dewatering rates and greater retention of fine sediments. Recently, however, momentum has begun to shift towards the use of sustainable materials. Natural flocculants, such as starch and chitosan, are increasingly being tested as an attractive alternative to synthetic polymers. Researchers have identified a number of natural flocculants, polysaccharides and polysaccharide derivatives in particular, as candidates for dewatering applications. In this study, the dewatering performance of four soils (sand, silt, kaolin, and natural organic soil) was evaluated with synthetic and starch-based flocculants. Dewatering performance of five cationic starch-based polymers with charge densities ranging from 0.38 to 0.94 meq/g and molecular weights ranging from 5 x 10(4) g/mol to 5 x 10(5) g/mol were compared with five cationic acrylamide-based polymers with charge densities that ranged from 1 to 3.05 meq/g and molecular weights that ranged from 10 x 10(6) to 20 x 10(6) /mol. The cationic polyacrylamides and cationic starches were selected with a wide range of charge densities and molecular weights in order to study the effect of flocculant properties on the flocculation and dewatering performance of the used soils. The optimum dose of each flocculant was determined using the jar test. Additionally, pressure filtration tests were performed to determine the dewatering rates and filter cake properties. Test results showed that the flocculants' properties, especially charge density, have a significant effect on the optimum dose. The optimum doses of the cationic starch flocculants were two to four times higher than the cationic polyacrylamide polymers. Additionally, it was found that the cationic starches were more effective in minimising the turbidity of the natural organic soils than the cationic polyacrylamides. Finally, the cationic starches allowed for a 900% increase in dewatering rate in comparison with the soil samples that were tested without flocculants.
Keywords: Geosynthetics; Geotextile tube; Dewatering; Cationic starch; Cationic polyacrylamide; SEPARATION; BEHAVIOR; Engineering; Geology; Materials Science